Effects of different dietary levels of AFB1 on survival rate and growth factors of Beluga (Huso huso) - Sepahdari, A.; Ebrahimzadeh Mosavi, H. A.; Sharifpour, I.; Khosravi, A.; Motallebi, A. A.; Mohseni, M.; Kakoolaki, S.; Pourali, H.R.; Hallajian, A. (2010)
In the present study, the impacts of various concentrations of Aflatoxin B1 (AFB1) on Beluga, Huso huso, under controlled conditions were investigated. Belugas (120±10g) were fed on diets containing 0, 25, 50, 75, and 100 ppb AFB1/kg of diet for 3 months. Results showed various levels of AFB1 do not significantly affect the specific growth ratio (SGR) (P<0.05) of fish in different treatments. However, weight gain and food conversion ratio (FCR) were varied significantly (P<0.05 between control and treatments with diets contaminated with 75 and 100ppb AFB1/kg after 90 days). The increase AFB1 level of did not affect on the percent of survival rate(SR) and no mortality was observed in treatments (SR=100%) suggesting that various AFB1 levels under experimental conditions of the present study affect some growth factors, such as, weight gain and FCR but have no significant impact on SR and SGR. Histopathological studies showed that different level of AFB1 can cause broad range of change in liver tissue, including progressive fat deposition, hepatocyte degeneration and necrosis, particularly at concentration of 75 and 100ppb AFB1/kg of diets after 60 days. Published